2010
DOI: 10.1002/art.27350
|View full text |Cite
|
Sign up to set email alerts
|

Failure of intravenous immunoglobulin to prevent congenital heart block: Findings of a multicenter, prospective, observational study

Abstract: Objective. Congenital heart block (CHB) is presumed to be caused by transplacental passage of maternal immunoglobulin against Ro and La ribonucleoproteins. The recurrence rate in subsequent pregnancies following the birth of a child with CHB is ϳ19%. The purpose of this study was to determine whether intravenous immunoglobulin (IVIG) therapy could prevent the development of CHB in the fetuses of high-risk pregnant women.Methods. A total of 24 pregnancies in 22 women who had a previous pregnancy in which CHB de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
83
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(90 citation statements)
references
References 14 publications
0
83
0
4
Order By: Relevance
“…120 The potential of IVIG to prevent CHF and to reduce proinflammatory cytokines has been shown in an experimental model of virus induced autoimmune myocarditis in experimental Chagas disease and in human DCM. [121][122][123][124][125][126] IVIG preparations are believed to bind to and neutralize circulating autoantibodies of diverse specifity.…”
Section: Autoantibodies As a Clinical Target For Therapy Of Heart Faimentioning
confidence: 99%
“…120 The potential of IVIG to prevent CHF and to reduce proinflammatory cytokines has been shown in an experimental model of virus induced autoimmune myocarditis in experimental Chagas disease and in human DCM. [121][122][123][124][125][126] IVIG preparations are believed to bind to and neutralize circulating autoantibodies of diverse specifity.…”
Section: Autoantibodies As a Clinical Target For Therapy Of Heart Faimentioning
confidence: 99%
“…International efforts have attempted to improve the understanding and management of this condition, with major contributions from different groups [8,12,[14][15][16][17][18][19]. However, registries are needed to improve our knowledge and the management of CHB.…”
Section: Introductionmentioning
confidence: 99%
“…Two recent multicenter prospective studies (one in Europe and one in the United States) demonstrated that IVIG given to mothers with a previous child with congenital AV block could not prevent recurrence of CAVB. 14,15 Most recently, a multicenter case-control study found that hydroxychloroquine, given to mothers with a previous child with cardiac neonatal lupus,…”
Section: Acquired Av Block Including Av Block In the Setting Of Acutementioning
confidence: 99%